2016
DOI: 10.1182/blood.v128.22.1834.1834
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Activity of Brentuximab Vedotin (BV) Plus Ifosfamide, Carboplatin, and Etoposide (ICE) for Relapsed/Refractory (Rel/Ref) Classical Hodgkin Lymphoma (cHL): Initial Results of a Phase I/II Trial

Abstract: Background: When initial therapy for cHL fails, the standard approach is multiagent salvage chemotherapy followed by autologous stem cell transplant (ASCT). The success of ASCT can be predicted by achievement of complete remission (CR) by fluorodeoxyglucose positron emission tomography (PET) following salvage chemotherapy (Moskowitz, et al. Blood 2012;119:1665-70). Unfortunately, about half of patients (pts) are unable to achieve CR with first salvage. The anti-CD30 antibody-drug conjugate BV is effective as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
2
33
0
5
Order By: Relevance
“…Concurrent administration of BV with cytotoxic chemotherapy would be expected to increase depth and durability of response in patients with functional status sufficient to receive combination therapy. BV has been feasibly combined with upfront 13,14 and second-line 15…”
Section: Resultsmentioning
confidence: 99%
“…Concurrent administration of BV with cytotoxic chemotherapy would be expected to increase depth and durability of response in patients with functional status sufficient to receive combination therapy. BV has been feasibly combined with upfront 13,14 and second-line 15…”
Section: Resultsmentioning
confidence: 99%
“…Results of the use of brentuximab vedotin in combination with conventional chemotherapy are also promising in this poor‐risk population of relapsed/refractory HL. A study assessing the efficacy of brentuximab vedotin in combination with bendamustine reported a CR rate of 74% (64% and 84% for refractory and relapsed patients, respectively) and an ORR of 93% (LaCasce et al , ), while brentuximab vedotin in combination with ICE produced ORR and CR rates of 94% and 88%, respectively (Cassaday et al , ). Treatment with a combination of brentuximab vedotin and ESHAP (etoposide, methylprednisolone, cytarabine, cisplatin) in patients with primary chemorefractory disease who were candidates for HDT and ASCT resulted in a pre‐transplant CR rate of 70% (Garcia‐Sanz et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Консолидация достигнутого после БВ эффекта с помощью ауто-или алло-ТГСК позволяет добиться долгосрочной ВБП, равной 32 и 48% соответственно. Сегодня одно из самых частых показаний для использования БВ -это подготовка к ТГСК [16,17]. В представленной работе мы также стремились закрепить достигнутый после БВ эффект с помощью ТГСК: у 5 пациентов консолидацию ремиссии проводили лучевой терапией.…”
Section: обсуждение результатов исследованияunclassified
“…В то же время у небольшой части пациентов с Р-Р ЛХ (около 10%) после монотерапии БВ удается получить длительную ремиссию и, возможно, излечение [13]. При комбинации БВ с химиотерапией общего ответа достигают 80-100% пациентов [16,17]. Назначение БВ и бендамустина в качестве второй линии терапии с последующей ауто-ТГСК позволяет добиться 2-летней ВБП в 62,6% случаев [18].…”
unclassified